Chemical Characteristics of Cereal Based on Local Food from Flores to Prevent Stunting - Nur R. Adawiyah Mahmud; Dewi Handayani; Ernawati (Nusantara Science and Technology Proceedings, 2023)
The program for providing additional nutritious based on local food is one of the stunting prevention strategies in East of Nusa Tenggara (NTT). Jagung titi is one of local food from Flores that has been known for long time. Although it is familiar for NTT community, not many publications have been found for its chemical characteristic. This research aimed to determine the chemical characteristic of cereal based on jagung titi (flaked corn) (CCF) and pumpkin flour (PF). This cereal was formulated from cracker corn flour and pumpkin flour in three compositions (90% CCF + 10% PF; 80% CCF + 20% PF; and 70%CCF + 30% PF). The proximate analysis of samples was using the AOAC method. CCF in 100 grams contains 76.18% carbohydrate, 9.03% protein, 2.18% fat, 0.96% ash, and 5.77% water. PF in 100 grams contains 43.9% carbohydrate, 12.53% protein, 5.35% fat, 7.14% ash, and 21.81% water. The chemical properties of cereal products can be affected by the formulation of CCF and PF. The third cereal composition (70% CCF + 30% PF) was the highest rate of acceptability by consumer panelists for the sweet flavor, aroma, and texture. This cereal product was promising as alternative nutritional local food to prevent stunting due to its effectiveness in presentation and consumption.